2017
DOI: 10.1128/mbio.01445-17
|View full text |Cite
|
Sign up to set email alerts
|

Erratum for Maler et al., “Key Role of the Scavenger Receptor MARCO in Mediating Adenovirus Infection and Subsequent Innate Responses of Macrophages”

Abstract: Affiliations i and l were given incorrectly. The affiliation line should appear as shown above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…2 c). In vitro experiments confirmed that only Ad-exposed wt, but not MARCO −/− alveolar macrophage-like MPI cells, the latter lacking the sensitizing IFN-αβ response to Ad [ 17 ], overproduce IFN-αβ following LPS stimulation (shown in Fig. 2 d).…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…2 c). In vitro experiments confirmed that only Ad-exposed wt, but not MARCO −/− alveolar macrophage-like MPI cells, the latter lacking the sensitizing IFN-αβ response to Ad [ 17 ], overproduce IFN-αβ following LPS stimulation (shown in Fig. 2 d).…”
Section: Resultsmentioning
confidence: 75%
“…S2, bottom left) or RPM ( Fig. 3 ) show impaired Ad uptake and IFN-αβ response ([ 17 ] and Fig. 2 b), which excludes an IFN-αβ-mediated autocrine sensitizing effect.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations